OPTIMIZATION OF A TRAINING PROCESS IN STRIKING KINDS OF COMBAT SPORTS DURING THE PRE-CONTEST STAGE (CASE STUDY: BOXING AND KICKBOXING) - Victor Lukyanenko; Ruslan Volikov (Вестник Северо-Кавказского федерального университета, 2022)
The article gives a detailed description of different views of scholars on the efficiency enhancing of a training process, preparation features at the pre-contest stage of kick-boxers and boxers of different tactical styles, weight categories and sport qualifications. The authors have developed and proposed new approaches for the organization of a training process at the pre-contest stage. The approaches are aimed at the improvement of individual physical abilities and individual technical competency of combat athletes using different tactical ighting styles.